The Relationship between Honey Yield and Environmental Pollutants in Turkey - Gungor Karakas; Hayriye Sibel Gülse Bal (Turkish Journal of Agriculture: Food Science and Technology)
In recent years, environmental pollution, climate change and excessive use of natural resources have caused problems in the ecosystem. Honey bees are among the most affected by this environmental pollution. Climate change and environmental pollutants cause irregularities in colony development, the formation of weak colonies, the spread of diseases, the inability to return to the hive of field bees, and their mortality and low productivity. Turkey ranks second after China in the production of honey in the world. Honey is a strategic product for Turkey. This study investigated the effect of some environmental pollutants on honey yield in Turkey. This study used the time series analysis covers the years 1990-2017. In the research, honey yield as dependent variable, as independent variables; methane (CH4), carbon dioxide (CO2), diazot oxide (N2O) release, pesticide, insecticide, fungicide, herbicide use and industrial production index were used. After the stationary of the series was tested with ADF Unit Root test, the relationship between the variables was examined by Johansen Co-integration analysis. The effect of environmental pollutants on honey yield was tested by the FMOLS analysis method. According to the FMOLS results, the increase of 1% pesticide use, CH4, CO2, and N2O resulted in a decrease in honey yield of 0.36%, 0.70%, 0.74%, and 0.37% respectively. On the other hand, the increase of 1% insecticide, fungicide, herbicide use and industrial production index caused 0.15%, 0.14%, 0.09% and 0.84% increase in honey yield, respectively.